Polyaniline hydrogel in flexible energy systems: Synthesis techniques, hybrid architecture, sustainability and techno-economic analysis - Parvez, Md. Shohan; Rahman, Md Mustafizur; Izan Izwan, Misnon; Samykano, Mahendran (Elsevier, 2025)
This review presents the progressive advances in polyaniline (PANI)-based conductive polymer hydrogels (CPHs) for next-generation flexible energy storage systems, revealing a significant improvement in synthesis methodologies, sustainable progress, and applications. The review demonstrates how surfactants, crosslinkers, co-polymerization, and binder-free formulations can effectively achieve superior electrochemical performance and mechanical solidity. The analysis uncovers the developments addressing key challenges like cycle stability and capacitance fading through novel hybrid architectures of PANI with emerging materials like MXenes, Graphene, and Carbon nanotubes. An exceptional specific capacitance of 936.8 F g−1 at 1 A g−1 and energy density reaching 40.98 Wh kg−1 is also observed from the assisted dynamically crosslinked PANI/PVA hydrogel sheet. Moreover, dual-doping strategies and controlled crystallinity have led to remarkable stability improvements, with capacitance retention exceeding 92 % after 10,000 cycles. Crucial correlations between synthesis parameters and performance metrics reveal that γ-radiation-induced synthesis can enhance elongation up to 1400 % while maintaining superior conductivity. The control of optimum porosity has enabled the development of high-mass-loading electrodes (>43.2 mg cm−2) with outstanding rate capability (92.7 % retention from 20 to 500 mA cm−2). Novel freeze-thaw-shrink treatments and self-healing mechanisms have produced mechanically robust devices capable of operating under extreme conditions (−30 °C∼90 °C). Sustainable production approaches incorporating bio-friendly dopants and electrolytes demonstrate reduced environmental impact. This work also emphasises the optimum synthesis strategies for production scalability from a techno-economic viewpoint. These findings establish a framework for developing cutting-edge flexible supercapacitors with significant implications for advanced portable electronics, wearable devices, and grid-scale energy storage solutions.